ANALYSIS OF THE USE OF ANTIMICROBIAL AGENTS IN CESAREAN SECTION FOR ANTIBIOTIC PROPHYLAXIS AND THERAPY (Uzbekistan Open Conference, 2025)
This article presents the results of an assessment of the practice of prescribing antimicrobial agents for antibiotic prophylaxis and antibiotic therapy during cesarean section, and also analyzes the pharmacoeconomic effectiveness of using antimicrobials in the prevention and treatment of infectious complications.